Seroprevalence and risk factors of Toxoplasma gondii infection in oral cancer patients in China: a case–control prospective study. Issue 15 (13th July 2018) - Zhou, N.; Zhang, X. Y.; Li, Y. X.; Wang, L.; Wang, L. L.; Cong, W.
Abstract: Over the recent years, potential associations between Toxoplasma gondii ( T. gondii ) infection and cancer risk have attracted a lot of attention. Nevertheless, the association between T. gondii infection and oral cancer remains relatively unexplored. We performed a case–control study of 861 oral cancer patients and 861 control subjects from eastern China with the aim to detect antibodies to T. gondii by enzyme-linked immunosorbent assay (ELISA) in these patients. The results showed that oral cancer patients (21.72%, 187/861) had a significantly higher seroprevalence than control subjects (8.25%, 71/861) ( P < 0.001). Among them, 144 (16.72%) oral cancer patients and 71 (8.25%) control subjects were positive for IgG antibodies to T. gondii, while 54 (6.27%) oral cancer patients and 9 (1.05%) controls were positive for IgM antibodies to T. gondii . In addition, multiple logistic analysis showed that T. gondii infection in oral cancer patients was associated with blood transfusion history, keeping cats at home, and oyster consumption. To our knowledge, this is the first study that provided a serological evidence of an association between T. gondii infection and oral cancer patients. However, further studies are necessary to elucidate the role of T. gondii in oral cancer patients.